Development of groundnut shells and bagasse briquettes as sustainable fuel sources for domestic cooking applications in Uganda - Lubwama, Michael; Yiga, Vianney Andrew (Renewable Energy, 2017)
In this study groundnut shells and bagasse briquettes from agricultural wastes were developed with cassava and wheat starch binders using low pressure and high pressure techniques. In the low pressure technique, briquettes were produced after carbonization of groundnut shells and bagasse. The resulting bio-char was mixed with 30, 50, 70 and 90 grams of cassava and wheat flour starch binder for each 1000g of groundnut shells and bagasse bio-char. Groundnut shell briquettes were also developed under high pressure (230 MPa) using groundnut shells (1000g) without a binder, groundnut shells (1000g) with cassava flour starch binder (250g) and groundnut shells with wheat flour starch binder (250g). Thermo-physical properties of the briquettes were determined using thermo-gravimetric analysis. A Bomb calorimeter was used to determine the higher heating values of the briquettes. Thermal characteristics were determined by observing the flame temperature during combustion. The mechanical integrity of the briquettes was determined using the drop test method. The higher heating values for groundnut shell and bagasse briquettes developed using low pressure techniques were between 21 and 23 MJ/kg for both cassava and wheat starch binders. The results were all above the 16 MJ/kg average recorded for non- carbonized groundnut shell briquettes developed under high pressure.
Keywords: Bagasse; Binder; Briquettes; Groundnut shells; Drop Strength; HHV